Microscale electromagnetic actuation of ferrofluid for enhanced cooling efficiency - Tang, Jiawei; Luk, Patrick Chi-Kwong (Institute of Electrical and Electronics Engineers (IEEE), 2023)
Efficient cooling solutions can greatly enhance the performance and reliability of electronic systems. Traditional cooling methods have been well-developed, but most are based on not highly efficient cost effective conduction heat exchange. Improving heat exchange efficiency at low cost is a crucial task for all cooling applications. In this paper, we propose a novel method to improve heat exchange efficiency based on ferrofluid, a fluid with ferromagnetic properties, as a coolant. As a result, conduction heat exchange can be easily transformed into convection heat exchange in a passive manner with no additional energy required, significantly increasing cooling efficiency at a relatively low cost. A cooling system using ferrofluid as a coolant is designed and applied to a multi-junction ,or concentrated, photovoltaic and thermal (CPV/T) system through CFD modelling. Novel unsteady flow is generated resulting in higher thermal efficiency. Since ferrofluid is a nanoparticle, the proposed cooling method can be downsized to micro- or nano-scales for potential applications in many new areas.
Keywords: Special Machines; Electromagnetic Actuators and Sensors; ferrofluid; thermal management; cooling system; CPV